A comprehensive evaluation of the effect of different control valves on the dynamic performance of a recompression supercritical CO2 Brayton cycle. (1st June 2022) - Bian, Xingyan; Wang, Xuan; Wang, Rui; Cai, Jinwen; Tian, Hua; Shu, Gequn; Lin, Zhimin; Yu, Xiangyu; Shi, Lingfeng
Abstract: Supercritical CO2 Brayton cycle (SCBC) is regarded as one of the most promising power cycles due to its compactness and high efficiency. Considering the safe operation and the rapidly load tracking, the valve control is used to investigate the dynamic performance of the SCBC. Therefore, this paper establishes a dynamic model of a recompression SCBC and puts forwards five kinds of control valves to investigate and compare the influence of different control valves on the open-loop dynamic performance of the system from the thermodynamic response characteristics and the safety performance evaluation. The simulation results indicate that the turbine bypass valve and the HTR bypass valve have a better load regulation capability compared with the other valves: load rates of 40.87% and 52.33% can be achieved when the valve opening is reduced to 50%, respectively. Besides, the two valves allow for timely tracking and maintain safe system operation simultaneously with up to two additional controllers. Moreover, the system under the turbine bypass valve control has the fastest response compared with that under the control of turbine throttle valve and HTR bypass valve. Highlights: A dynamic model of a recompression SCBC is developed. 2.The open-loop performance of control valves are compared comprehensively. The closed-loop performance of optimized valves are investigated. The turbine bypass valve and the HTR bypass valve perform optimally.